THE INTEGRATION OF INFORMATION SYSTEMS AND FOREIGN TRADE: TECHNOLOGICAL CHALLENGES IN MODERN CUSTOMS MANAGEMENT - Silva, Diego Bassan (Revista Sistemática, 2022)
The increasing complexity of global trade and customs regulations has intensified the need for robust integration between information systems and foreign trade operations. Digital transformation in customs management has shifted organizational and governmental practices toward the adoption of Enterprise Resource Planning (ERP) systems, specialized trade compliance software, and automated process technologies. This study examines the role of integrated information systems in modern customs management, with particular emphasis on process automation, regulatory compliance, and operational risk mitigation. By consolidating transactional data and embedding compliance logic into enterprise workflows, integrated systems enhance transparency, accuracy, and real-time visibility across international supply chains. However, technological integration also presents significant challenges, including system interoperability, regulatory heterogeneity, data governance, and organizational readiness. The analysis highlights how automated and data-driven approaches support risk-based customs controls while facilitating legitimate trade flows. The findings suggest that effective integration of information systems is not solely a technological endeavor but a strategic process requiring alignment between digital infrastructures, regulatory frameworks, and human capabilities to achieve sustainable and compliant foreign trade operations.